Microbiota of Greenhouse Soils in Wheat Selection - Dubovyi, V.I.; Dubovyi, O.V.; Adamovych, I.V.; Pyda, S.V.; Patyka, V.P.; Дубовий, В.І.; Дубовий, О.В.; Адамович, І.В.; Пида, С.В.; Патика, В.П. (PH "Akademperiodyka" of the NAS of Ukraine, 2025)
A system of agrotechnical and reclamation works is used to obtain a high-yielding and high-quality selection wheat. These works result in significant changes in both the components of the original landscape and the whole complex. It is known that the quantitative and qualitative composition of soil microbiota adequately reflects the degree of anthropogenic load, therefore it is used as a diagnostic indicator when estimating the ecological state of soil. The aim of this work was to analyze the soil microbiota of the phytotron-selection complex of the V.M. Remeslo Myronivskyi Wheat Institute using various agricultural technologies to obtain high-quality breeding material for winter wheat (Triticum aestivum L.). The specialization of this plant-breeding center was instrumental in using grow rooms according to the monoculture phylum. Methods. Classical microbiological and statistical techniques were used in the research. Microbiological analyses were performed by the technique of dilution of soil suspensions using nutrient-selective media. The total number of ammonifying, spore-forming bacteria, streptomycetes, bacteria that absorb mineral nitrogen, oligonitrophilic and cellulose-destroying microorganisms, microscopic fungi, as well as bacteria growing on agar soil, was taken into account. Microbial biomass was calculated on the basis of data on the number and size of cells, taking their specific gravity at 1.08 g/cm3. Indicators of the frequency and density of species were used to determine typical and dominant species. Additionally, the qualitative composition of bacteria, microscopic fungi, and streptomycetes has been determined. Results. It has been established that use of cattle manure at a rate of 100 t/ha as well as the cultivation of break crops (radish, winter bird rape) has positive effects on the biological activity of soil and the biomass of soil microorganisms. The intensity of СО2 emission in this variant with fertilisization was 2.5 times higher than in control. Similar patterns were observed for О2 absorption. It was noticed that the processes of mineralization of the organic component of grow rooms soil are more active than in a field. The mechanism of managing the microbiological condition of greenhouse soil through the introduction of crop rotation of vegetables (cucumber, tomato) and medicinal tropical crops (kalanchoe), break crops (radish, winterbirdrape) and the application of organic fertilizers and growing green manure had a positive effect on the quality of winter wheat. The mastered crop rotation in these facilities was carried out without using electricity to maintain light and temperature conditions of cultivation. It has been established that the index of earth-balls biofouling with azotobacter did not change in these constructions over the research period. The dynamics of the amount of streptomycetes, myxomycetes, and spore bacteria testifies to the fact that, on the average, these indices in the grow rooms and in the field do not significantly differ. Conclusions. The microbiological analysis of soil in the grow rooms and the research results show that it is expedient to introduce crop rotation in grow rooms. Unlike field conditions, where the study of microbiological relationships in the system "soil - microorganism - plant" determines soil fertility trends, in the artificial climate of knowledge and management of such relationships will largely determine the success of breeding practice, including obtaining high-quality primary breeding material of winter wheat and will significantly increase the profitability of the use of such objects of artificial climate.